Is It Possible to Mitigate Fear of Fireworks in Dogs? A Study on the Behavioural and Physiological Effects of a Psychoactive Supplement - Daniela Ramos; Karina V. B. Yazbek; Amanda C. Brito; Barbara Georgetti; Luisa M. L. Dutra; Fabiola O. P. Leme; Angélica S. Vasconcellos (Animals, 2024)
Canine fear of fireworks is a common problem worldwide, with serious implications for the welfare of both dogs and their owners. Therapies for the problem are available, and herbal and nutraceutical agents are increasingly suggested by professionals; nonetheless, studies on their real efficacy in reducing firework fear are lacking. In a randomised, double-blinded, placebo-controlled study, 44 dogs (25 in the “supplement” group and 19 in the “placebo” group) completed a long-term continuous treatment with either a supplement made of tryptophan, valerian, and passiflora or a placebo, including two real exposures to fireworks (on 2020 Christmas and 2021 New Years’ Eve, after 42 and 48 days of treatment, respectively). Owners of both groups received the same general environmental management and food/toy offering recommendations for trying with their dogs on those nights. Behavioural (measured by LSSS—Lincoln Sound Sensitivity Scale and PANAS—Positive and Negative Activation scale, as rated by the owners) and stress (measured via salivary cortisol measures) reactions were evaluated. Significantly greater fear decrease (LSSS) was recorded in the “supplement” dogs, as compared to the “placebo” group. Cortisol dosages on New Year’s Eve (“noisy” night) were in line with behavioural results; “supplement” dogs showed a smaller increase in the stress response from 22:30 to 00:30 h on New Year’s Eve and a greater decrease in their stress response from 02:30 h to 10:30 h on New Year’s Day compared to “placebo” dogs. Smaller cortisol levels were also shown by “supplement” dogs than “placebo” dogs on a controlled “quiet night” (27th December). Owners’ rates on PANAS remained stable during the whole period of therapy for both groups. The evaluated supplement, a combination of tryptophan, valerian, and passiflora, showed satisfactory results and rare side effects when treating dogs fearful of fireworks.